9514 1404 393
Answer:
A
Step-by-step explanation:
The function f(x) is required in the numerator, eliminating choices C and D.
The restriction is that function g cannot be zero, so we cannot have ...
3x +2 = 0
3x = -2
x = -2/3 . . . . . eliminates choice B; confirms choice A
Answer:
2C + 10
Step-by-step explanation:
Answer:
13 and 5
Step-by-step explanation:
x+y=18
x-y=8
_____
2x=26
x=13
So the first number must be 13
13+y=18
y=5
And the second number must be 5
Answer:
A) 0 (no solutions)
Step-by-step explanation:
Solve the equation:
3x - 10(x+2) = 13 - 7x
3x - 10x -20 = 13 - 7x
-7x - 20 = 13 - 7x
-20 = 13
Since both sides are clearly not equal to each other, no solution can satisfy both sides to be equal to each other. So A is correct.